Active cell balancing control strategy for parallel connected LiFePO4 batteries - Buswig, Yonis.M.Yonis; Md Ohirul, Qays; Md Liton, Hossain; Md Momtazur, Rahman; Ahmed, Abu-Siada (China electric power research institute, 2020)
While several recent studies have focused on eliminating the imbalance of energy stored in series-connected battery cells, not much attention has been given to balance the energy stored in parallel-connected battery cells. As such, this paper aims at presenting a new balancing approach for parallel LiFePO 4 battery cells. In this regards, Backpropagation Neural Network (BPNN) based technique is employed to develop a Battery Management System (BMS) that can assess the charging status of all cells and control its operation through DC/DC Buck-Boost converter. Simulation results reveal the effectiveness of the proposed approach in balancing the energy stored in parallel-connected battery cells in which the state of charge (SoC) estimation error is found to be only 1.15%.